Feasibility of longitudinal monitoring of atherosclerosis with pulse wave imaging in a swine model. (28th December 2021) - Kemper, Paul; Nauleau, Pierre; Karageorgos, Grigorios; Weber, Rachel; Kwon, Nancy; Szabolcs, Matthias; Konofagou, Elisa
Abstract: Objective. Atherosclerosis is a vascular disease characterized by compositional and mechanical changes in the arterial walls that lead to a plaque buildup. Depending on its geometry and composition, a plaque can ruptured and cause stroke, ischemia or infarction. Pulse wave imaging (PWI) is an ultrasound-based technique developed to locally quantify the stiffness of arteries. This technique has shown promising results when applied to patients. The objective of this study is to assess the capability of PWI to monitor the disease progression in a swine model that mimics human pathology. Approach. The left common carotid of three hypercholesterolemic Wisconsin miniature swines, fed an atherogenic diet, was ligated. Ligated and contralateral carotids were imaged once a month over 9 months, at a high-frame-rate, with a 5-plane wave compounding sequence and a 5 MHz linear array. Each acquisition was repeated after probe repositioning to evaluate the reproducibility. Wall displacements were estimated from the beamformed RF-data and were arranged as spatiotemporal maps depicting the wave propagation. The pulse wave velocity (PWV) estimated by tracking the 50% upstroke of the wave was converted in compliance using the Bramwell–Hill model. At the termination of the experiment, the carotids were extracted for histology analysis. Main results. PWI was able to monitor the evolution of compliance in both carotids of the animals. Reproducibility was demonstrated as the difference of PWV between cardiac cycles was similar to the difference between acquisitions (9.04% versus 9.91%). The plaque components were similar to the ones usually observed in patients. Each animal presented a unique pattern of compliance progression, which was confirmed by the plaque composition observed histologically. Significance. This study provides important insights on the vascular wall stiffness progression in an atherosclerotic swine model. It therefore paves the way for a thorough longitudinal study that examines the role of stiffness in both the plaque formation and plaque progression.